Bibliometric analysis of diagnostic yield of CT pulmonary angiogram (CTPA) in the diagnosis of pulmonary embolism (PE) - Ren, Yi Kow; Razali, Khairiah; Chooi, Leng Low; Siron @ Baharom, Khairul Nizam; Zakaria@Mohamad, Zamzuri; Mohd Yusof, Mubarak; Md Ralib @ Md Raghib, Ahmad Razali (Springer Nature Group, 2023)
CT pulmonary angiography (CTPA) is the investigation of choice for diagnosing pulmonary embolism (PE). Due to the speed and ease of performing the CTPA scans, more clinicians are becoming overly reliant on them, even for patients without strong suspicion of PE. We conducted a bibliometric analysis on the PubMed database from 1990 to 2022 to investigate the literature on the diagnostic yield of CTPA in the diagnosis of PE. A total of 166 articles were published in 98 journals. The number of publications has steadily increased since 2010 and peaked in 2020. Authors from 24 countries contributed to these publications, with the overwhelming majority emanating from United States of America, totaling 66 articles. The authors’ contributions were relatively well spread out, with the top four authors publishing the highest number of articles at six each. When we investigated the collaboration between the authors, we found limited multinational and multi-institutional collaborations on this topic. Therefore, more multinational and multi-institutional collaborations will be valuable in future studies. In conclusion, this bibliometric analysis summarizes the literature on diagnostic yield of CTPA in the diagnosis of PE and sheds light on the future pathway that researchers and institutions can focus on.